The World Model of the Historical Buddha - Knoll, Meinhard (2019)
This work presents the world model of the historical Buddha that represents the five aggregates of grasping, which form the core of the First Noble Truth in Buddhism. The model operates based on a dukkha potential field, with pairs of internal and external sense bases. The magnitudes of attractive and repulsive influences of pleasant and unpleasant sense objects, respectively, are defined by their dukkha potentials. Volition is derived from the model as the gradient of the dukkha potential providing the driving forces of attraction and repulsion. Inclinations and disinclinations in the dukkha potential field are a result of a programming process by repetitive thinking and pondering. Experiments with the model confirm its functionality. Internal and external sense bases merge in the metta state of loving-kindness, and the transition into a meditative jhana state puts the model elements out of service. This model is a novel translation from the Pali Canon that provides scientific clarity of the suttas and addresses natural science-oriented readers.Permalinkhttps://nbn-resolving.de/urn:nbn:de:hbz:6-94169655129ISBN978-3-8405-0213-2Paperback, III, 55 Seiten